Loss of PRC2 subunits primes lineage choice during exit of pluripotency - Chet H. Loh; Siebe van Genesen; Matteo Perino; Magnus R. Bark; Gert Jan C. Veenstra (Nature Communications, 2021)
Polycomb Repressive Complex 2, an important regulator of embryonic development, exists in two configurations, PRC2.1 and PRC2.2. Here the authors dissect the functional contributions of these two PRC2 subunits and observed complex-specific alterations in the cell state of pluripotent and early differentiating cells.